Mathematical Modeling of Fluid Flow and Heat Transfer in Petroleum Industries and Geothermal Applications - Massoudi, Mehrdad (MDPI - Multidisciplinary Digital Publishing Institute, 2020)
Geothermal energy is the thermal energy generated and stored in the Earth's core, mantle, and crust. Geothermal technologies are used to generate electricity and to heat and cool buildings. To develop accurate models for heat and mass transfer applications involving fluid flow in geothermal applications or reservoir engineering and petroleum industries, a basic knowledge of the rheological and transport properties of the materials involved (drilling fluid, rock properties, etc.)-especially in high-temperature and high-pressure environments-are needed. This Special Issue considers all aspects of fluid flow and heat transfer in geothermal applications, including the ground heat exchanger, conduction and convection in porous media. The emphasis here is on mathematical and computational aspects of fluid flow in conventional and unconventional reservoirs, geothermal engineering, fluid flow, and heat transfer in drilling engineering and enhanced oil recovery (hydraulic fracturing, CO2 injection, etc.) applications.